Representação a contrapelo: o desenho de arquitetura como ferramenta da produção do espaço - Tiago Amaral da Silva (2022)
This dissertation aims to discuss the ambivalent condition of architectural representations as auxiliary instruments of the production of space. On one hand, they can be used as tools to control the production at the service of capital, bringing together the fragmented work of construction manufacturing workers, in order to guarantee the extraction of surplus value. For this, they are configured as a code, that is restrict to the field of architects. On the other hand, they have the potential to be applied in operational practices that promote the interaction between construction site and design, to assist in the dissemination of technical information beyond the restricted limits that they currently perform in the field of architecture, or to be critically appropriated by marginalized individuals and socio-spatial groups. Based on these assumptions, I recognize that representations are not neutral tools, and therefore they can be used for different purposes with different modes of mobilization. This research analyzes this ambivalence based on case studies of different architectural practices, investigating from the most conventional to those that, in some way, deviate from the hegemonic arrangement (such as technical advisory for participative processes of self-management housing groups, for the popular demands or for the self-construction). Thus, in the research presented in this text, I criticize the prescriptive and codified use of representations and I investigate the extent to which they are able to be used in instruments of dialogue: tools that are oriented towards critical interaction and exercises of emancipation of the agents that mobilize them or towards whom they are directed.